PENGARUH ECCENTRIC HAMSTRING EXERCISE TERHADAP PENINGKATAN KECEPATAN BERLARI PADA PEMAIN SEPAKBOLA (Studi Literatur) - Taufik Hidayat; Ari Sudarsono; Rovika Trioclarise (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: Football is one of the most popular sports in the world, including Indonesia, where soccer athlete is required to be able to play football quickly and precisely so that speed when running is an important factor in football players, eccentric hamstring exercise is one of the physiotherapy interventions that can be done to improve the strength and flexibility of hamstring muscles so as to increase the running speed of football players. Purpose: To determine the effect of giving eccentric hamstring training on increasing running speed. Study Design: Literature study. Data sources: PubMed (National Library of Medicine), PMC (Pubmed Central),Semantic Scholar and Elsevier Journal Of Body Work. The Eligibility Criteria of Literature: eccentric hamstring training, football players, clinical trial research, published in 2011-2021, the outcome is an increase in running speed using sprint time intervals and free access literature. Results: There are 8 literatures that have fulfilled the criteria. The research was conducted by measuring the running speed of football players using the same method. The entire literature uses the eccentric hamstring exercise intervention to increase running speed in soccer players. Conclusion: The eccentric hamstring exercise intervention has effect on increasing running speed in soccer players.